(untitled) (Conferencea, 2022)
This article is devoted to the possibilities of wider use of practical methods in chemistry education, the organization of experiments suitable for the topics being taught, limited only to theoretical methods. Such approaches increase students’ interest in science and help to form creative, critical, creative thinking skills.